INQUIRY-BASED LEARNING TRAINING AS A PEDAGOGICAL COMPETENCE IMPROVEMENT OF MTS. NURUL HUDA TEACHERS - Mohamad Anas; Millatuz Zakiyah; Triya Indra Rahmawan; Mokhamad Rohma Rozikin (UPT. PKM UB, 2022)
Based on the 2018 PISA report, the literacy and analytical abilities of Indonesian students are still very low. Poor literacy and analytical competence can be one of the factors that cause the low comprehension ability of Indonesian students in understanding and reading information. One method that has been proven to improve students' competence and skills, especially in analytical skills and increase students' curiosity is inquiry-based learning. Unfortunately, not all teachers have the pedagogical competencies needed to conduct inquiry learning. This problem is also seen in teachers in MTs. Nurul Huda Malang. Therefore, this community service activity is carried out to increase the capacity and pedagogical competence of teachers to improve the quality of learning that can trigger analytical attitudes in students. The implementation of service is carried out through several stages, namely: surveys and learning observations, training syllabus design, training implementation, and training evaluation. From the results of the implementation evaluation, it is known that the inquiry learning training is very useful and can be immediately applied by the teacher. In addition, there are other opportunities in the future to carry out training related to digital learning media needed by teachers in MTs. Nurul Huda Malang.